Surgical and functional outcomes of robot-assisted versus laparoscopic partial nephrectomy with cortical renorrhaphy omission - Masashi Kubota; Toshinari Yamasaki; Shiori Murata; Yohei Abe; Yoichiro Tohi; Yuta Mine; Hiroki Hagimoto; Hidetoshi Kokubun; Issei Suzuki; Naofumi Tsutsumi; Koji Inoue; Mutsushi Kawakita (Scientific Reports, 2022)
Abstract To evaluate the surgical and functional outcomes between robot-assisted (CRO-RAPN) vs. laparoscopic (CRO-LPN) methods of cortical-renorrhaphy-omitting partial nephrectomy. Between July 2012 and June 2020, patients with localized clinical T1-2 renal masses who underwent CRO-RAPN or CRO-LPN were reviewed. The outcomes of the two groups were compared using propensity-score matching. Trifecta was defined as negative surgical margin, warm ischemic time < 25 min, and absence of complications of Clavien-Dindo grade III or more until three months postoperatively. The preservation rate of the estimated glomerular filtration rate (eGFR) was evaluated at six months postoperatively. Among 291 patients (CRO-RAPN, n = 210; CRO-LPN, n = 81) included in the study, 150 matched pairs of patients were analyzed. Compared to the CRO-LPN group, the CRO-RAPN group was associated with shorter warm ischemic time (13 min vs. 20 min, P < 0.001), shorter total operation time (162 min vs. 212 min, P < 0.001), less estimated blood loss (40 mL vs. 119 mL, P = 0.002), lower incidence of overall complications (3% vs. 16%, P = 0.001), higher preservation rate of eGFR at six months postoperatively (93% vs. 89%, P = 0.003), and higher trifecta achievement rate (84% vs. 64%, P = 0.004). CRO-RAPN contributed to shorter warm ischemic time, less blood loss, fewer complications, and higher preservation of renal function, all of which allowed this technique to achieve a higher rate of trifecta compared to CRO-LPN.